(untitled) (Medicine Today, 2020)
Introduction: Renal involvement is frequent in neonates with perinatal asphyxia. It is correlated with the severity of neurological damage and degree of involvement depends upon the severity of asphyxia. To assess the status of renal function in new born suffering from prenatal asphyxia and to precise the relationship between severity cerebral damage and renal failure. Materials and Methods: A hospital based cross-sectional study was conducted in the department of Neonatology, Chattogram Maa O Shishu Medical College Hospital, Agrabad, Chattogram on 180 full-term neonates (150 cases and 30 control). The cases were categorized according to HIE Sarnat stages. Results: Among cases, 83(53.4%) were with HIE I, 53 (35.3%) were HIE II and 14(9.3%) were HIE III. The mean value of S. Creatinine was high in cases 1.64 ± 0.33 mg/dl vs 0.41 ± 0.09 mg/dl (p value <0.001) and it is highest in HIE stage III 1.85 ± 0.20 mg/dl (p value is <0.001). Mean Serum Potassium was high in cases 5.88 ± 0.59 mmol/L vs 3.99 ± 0.36 (p value <0.001) and the values are abnormally high in HIE stage III 6.25 ± 0.33 (p value <0.001). The mean value of FeNa was high in cases 2.44 ± 0.55 compared with control 1.06 ± 0.38 (p value <0.001) and it is higher in HIE stage III 2.72 ± 0.22 (p value is <0.001). Conclusion: Severity of renal impairment correlates well with the degree of HIE. HIE stage wise assessment of renal function status using serum creatinine level, S. potassium, FeNa, can be used to assess the outcome of perinatal asphyxia. Medicine Today 2020 Vol.32(1): 48-51